Sistem Perancangan Monitoring Inravena (Infus) Berbasis Internet Of Things - Raditya Frandika Irawan; Agung Kharismah Hidayah; Diana Diana; Dedy Abdullah (Jurnal Media Infotama, 2024)
Giving drugs or fluids into the body through the mouth will enter the digestive process first so that it is not quickly absorbed by the body is a process of fluid entry or commonly called infusion. Infusion is done by inserting a small needle into the blood vessel flow with absorption speed depending on the patient's body condition and the disease suffered, therefore the infusion needs to be controlled when attached. The purpose of this study is to control the infusion system with the application of technology to support health facilities by building an automatic and portable intravenous fluid monitoring system using Telegram. This tool can also send notifications through buzzer alerts and Telegram Bot notifications so that it can be applied to information on services, treatment and registration systems at hospitals online. From the results of the study, several conclusions can be drawn, namely, the Intravenous Monitoring System is able to monitor the condition of the infusion using the Telegram application, by testing using 3 infusion bags with 500ml liquid each the device can measure infusion capacity data well, from the tests carried out obtained Telegram notification delay with an average of 5 seconds, but this can be influenced by internet network conditions, From the tests that have been done, the author concluded that the accuracy rate in this study was 98%.